THE EFFECT OF THE PROBLEM-BASED LEARNING (PBL) MODEL INTEGRATED WITH SNAKES AND LADDERS MEDIA ON THE IPAS LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS - Arisania, Dinda; Izzatika, Amrina; Fernando Rizqi, Yoga; Khairani, Fadhilah (PROGRES PENDIDIKAN, 2025)
This study aimed to examine the impact of the Problem-Based Learning (PBL) model assisted by the snakes and ladders media on the learning outcomes of fifth-grade students in the IPAS subject. The research method used was a quasi-experimental group design, specifically the nonequivalent control group design. The population and sample consisted of 40 students. Data were collected through tests, observations, interviews, and documentation. The hypothesis was tested using simple linear regression analysis. If the significance result was 0.00 < 0.05, then the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. The results showed that there was a significant effect of the implementation of the PBL model assisted by the snakes and ladders media on the IPAS learning outcomes of fifth-grade students at SD Negeri 10 Metro Timur. This research indicated that the problem-based learning model integrated with educational game media had the potential to be an effective learning approach to improve students' learning outcomes at the elementary school level.